TINGKAT KEMAMPUAN SMASH SISWA PADA EKSTRAKURIKULER BOLA VOLI DI SMPN 17 BANDA ACEH - salbani, salbani; Munzir, Munzir; Subhananto, Aprian (Universitas Syiah Kuala, 2023)
Volleyball development is part of the development of quality human resources. It is a responsibility for all of us to pay special attention to education, especially in basic education, because it is the initial milestone in the formation of the character of students. This study aims to determine the level of Samsh's ability of volleyball extracurricular participants at SMP Negeri 17 Banda Aceh. This research is a quantitative descriptive research. The data collection techniques used are tests and measurements. The population in this study was all volleyball extracurricular participants at SMP Negeri 17 Banda Aceh with a total of 9 people. The sample in this study was all volleyball extracurricular participants at SMP Negeri 17 Banda Aceh with a total of 9 people. The instrument used in this study is by means of a test, namely the Smash test according to the Ministry of Education and National Education book. The data analysis technique used is percentage descriptive analysis. The results showed that the level of Smash ability category was either 0 students or 0%, either 4 students or 44%, medium 3 students or 34%, less 2 students or 22% and less once 0 students or0%.